General Principles and Challenges of Public Administration Organization in the Czech Republic - Potěšil, Lukáš; Svoboda, Tomáš (General Principles and Challenges of Public Administration Organization in Central Europe, 2024)
This chapter provides an overview of the organization of public administration in the Czech Republic. It can be traced back to more than four decades of communist totalitarian rule, which prohibited self-governance and established a State based on central management. A territorial and interest- based self-government was re-established after 1989, with substantial changes introduced in the organization of public administration. At the outset, this paper presents the general theoretical and legal background of the organization of public administration and its principles. The key aspect here is that the organization of public administration in the Czech Republic is based on the co-existence of local self-government and State administration. Therefore, a mixed public administration model is applied, under which authorities of territorial self-government units, in addition to exercising their independent competence (self-government), are entrusted with performing State administration as part of their delegated competence. Possible considerations regarding the future organizational structure of public administration in the Czech Republic have also been included.KEYWORDS administrative authority, delegated competence, municipalities, public administration, regions, self-government, State administrationBibliographyBobek, M., Molek, P., Šimíček, V. (eds.) (2009) Komunistické parvo v Československu: kapitoly z dějin bezpráví. Brno: Masarykova univerzita.Cogan, R. (2018) Zákon o krajích: komentář. 2nd edn. Praha: Wolters Kluwer.della Cananea, G., Ferrari Zumbini, A., Pfersmann, O. (eds.) (2023) The Austrian Codification of Administrative Procedure Diffusion and Oblivion (1920–1970). Oxford: Oxford Universit y Press; https://doi.org/10.1093/oso/9780198867623.001.0001.Furková, P., Veselý, M., Chodúr, P., Štěpánová, B. (2022) Obecně závazné vyhlášky v praxi obcí. Praha: C. H. Beck.Havlan, P., Janeček, J. (2014) Majetek územních samosprávných celků v teorii a praxi. 2ndedn. Praha: Leges.Havlan, P., Janeček, J. (2016) ‘Territorial Self-Governing Units of the Czech Republic as Entities Possessing Ownership and Other Proprietary Rights (the Basic Conceptual Issues)’, DANUBE: Law and Economics Review, 7(2), pp. 105–121 [Online]. Available at: https://doi.org/10.1515/danb-2016-0006 (Accessed: 11 October 2024).Hendrych, D., Kavěna, M., Pavlík, M. (2014) Správní věda. Teorie veřejné správy. 4th edn. Praha: Wolters Kluwer.Jan, B., Stanislav, P., Josef, V., Luboš, V. (2008) Zákon o obcích (obecní zřízení): komentář. Praha: C.H. Beck. Kadečka, S. (2003) Právo obcí a krajů v České republice. Praha: C.H. Beck. Knapp, V. (1995) Teor ie práva. Praha: C. H. Beck. Kopecký, M. (2017) Právní postavení obcí a krajů – základy komunálního práva. 2nd edn. Praha: Wolters Kluwer. Kopecký, M. (2023) Správní právo: obecná část. 3rd edn. Praha: C. H. Beck. Kopecký, M., Průcha, P., Havlan, P., Janeček, J., Balounová, J. (2022) Zákon o obcích: komentář; Zákon o Sbírce právních předpisů územních samosprávných celků a některých správních úřadů: Komentář. 4th edn. Praha: Wolters Kluwer. Malast, J. (2016) Teoretická východiska obecní samosprávy v České republice. Plzeň: Západočeská univerzita v Plzni. Merkel, A. (1931) Obecné právo správní. Díl první. Praha – Brno: Nakladatelství Orbis. Pospíšil P., Těžký, V., Glaser, L., Janeček, J., Lasáková, D., Novotný, A., Orszulíková, J., Venzara, D., Venzarová, P., Vymětal, M., Děvěrová, M., Havel, T., Jantač, P., Pejskarová, A., Radošínský, A. (2022) Zákon o krajích. Komentář. Praha: C. H. Beck. Potěšil, L., Furek, A., Hejč, D., Chmelík, V., Rigel, F., Škop, J. (2019) Zákon o obcích. Komentář. Praha: C. H. Beck. Pouperová, O. (2014) ‘Nezávislé správní úřady’, Správní právo, XLVII(4), pp. 209–226. Průcha, P. (2012) Správní právo: obecná část. 8th edn. Brno: Doplněk. Skulová, S., Petr, M., Soňa, S., Alena, K., Petr, H., Miloš, M., Lukáš, P., Petr, P., Jan, S. (2023) Základy správní vědy. 3rd edn. Brno: Masarykova univerzita.Sládeček, V. (2019) Obecné správní právo. 4th edn. Praha: Wolters Kluwer.Sládeček, V. (2019) Obecné správní právo. 4th edn. Praha: Wolters KluwerSvoboda, T., Skulová, S. (2023) ‘Několik poznámek k počtu obcí a jeho konsolidaci z pohledu práva’ in Svoboda, T., Skulová, S., Hejč, D. (eds.) Územní samosprávné celky v souvislostech správního práva. Pocta doc. JUDr. Petru Havlanovi, CSc. Brno: Masarykova univerzita.